(untitled) (Journal of Dhaka Medical College, 2021)
Aim: The study was undertaken with an objective to know the thyroid functions in Type 2 diabetics and to know the spectrum of thyroid dysfunction in Type 2 DM. Methods: The present study included 68OPD and IPD patients of Type 2 DM who attended the Department of General Medicine at Dhaka Medical College Hospital Dhaka. Detailed history and examination were done, fasting blood samples of all the subjects were taken and at the same time samples were tested for HbA1C and thyroid profile (T3, T4 and TSH). Result: in this study 68 established diabetics were screened for thyroid disorders by TFT. Abnormal thyroid function was found in 43 T2DM cases and remaining diabetics had normal thyroid function. Among 68 cases low thyroid function was noted in 20 patients and 18 subjects had Sub-clinical hypothyroidism. Hyperthyroidism was noted in 05 patients. Conclusion: Type 2 diabetes mellitus is a major problem all over the world and many patients of Diabetes Mellitus are associated with thyroid dysfunction. So diabetic patients s should be screened for thyroid disorder especially hypothyroidism. J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 149-152